2021
DOI: 10.35627/2219-5238/2021-29-8-63-68
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features of the Novel Coronavirus Disease in the Lipetsk Region in 2020

Abstract: Introduction: Due to a high incidence of the novel coronavirus disease (COVID-19) in the Russian Federation in 2020, identification of the regional features of the disease spread has become relevant for understanding of the further development of the development of the epidemic process, organizing and implementing comprehensive preventive measures. Objective. To study regional features of the COVID-19 epidemic process in the Lipetsk Region. Materials and methods. We used data from the Center for Hygiene and Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…According to our data, the importations of SARS-CoV-2 into Novosibirsk were not from China, but from Moscow, St. Petersburg, Yakutia (the northern region of Russia), as well as from Thailand and Spain. Similar results have been obtained for other Russian regions [10,11,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…According to our data, the importations of SARS-CoV-2 into Novosibirsk were not from China, but from Moscow, St. Petersburg, Yakutia (the northern region of Russia), as well as from Thailand and Spain. Similar results have been obtained for other Russian regions [10,11,[19][20][21][22].…”
Section: Discussionsupporting
confidence: 88%
“…The incidence structure in the first wave was also similar in Novosibirsk, Moscow [21], and Lipetsk [22]. The largest number of cases corresponded to the largest group, however, when normalized by the number of tests, it is revealed that the incidence in the group of 65 years and older exceeded the incidence rate in the other population groups.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The development of the pandemic in Russia is described for several regions, but it is hard to compare them since all articles cover different epidemiological and temporal aspects of the pandemic. The epidemiologic features of COVID-19 were described for Yakutia [ 7 ], the Lipetsk region [ 8 ] and the northwest of Russia [ 9 ]. The spread of the infection is influenced by important parameters of the region such as the age structure, the population density and size, transport links with other regions and countries, cultural characteristics, access to medical care and environmental factors [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%